2018
DOI: 10.3390/jmmp2040080
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water-Based Nanolubricants in Ultrasonic Vibration Assisted Grinding

Abstract: Currently, because of stricter environmental standards and highly competitive markets, machining operations, as the main part of the manufacturing cycle, need to be rigorously optimized. In order to simultaneously maximize the production quality and minimize the environmental issues related to the grinding process, this research study evaluates the performance of minimum quantity lubrication (MQL) grinding using water-based nanofluids in the presence of horizontal ultrasonic vibrations (UV). In spite of the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Meanwhile, synthetic ester produced less grinding force compared with biolubricants, with 22.8% and 22.9% reduction in the normal and tangential directions, respectively (Fig. 13 [127][128][129][130][131][132]). In the AISI 1018 grinding experiment of Shao et al [128], commercial vegetable oil was used in MQL, and the CoF was reduced from 0.299 to 0.271 compared with flood.…”
Section: Force and Cofmentioning
confidence: 99%
“…Meanwhile, synthetic ester produced less grinding force compared with biolubricants, with 22.8% and 22.9% reduction in the normal and tangential directions, respectively (Fig. 13 [127][128][129][130][131][132]). In the AISI 1018 grinding experiment of Shao et al [128], commercial vegetable oil was used in MQL, and the CoF was reduced from 0.299 to 0.271 compared with flood.…”
Section: Force and Cofmentioning
confidence: 99%
“…They concluded that surface roughness was high in MQL-assisted UAG when compared with the MQL-assisted CG. Molai et al 193 studied the effects of water-based nMQL-assisted UAG. The nanoparticles such as multiwalled carbon nanotubes, graphene oxide, Al 2 O 3 , graphite and hybrid Al 2 O 3 were used in their experimentations.…”
Section: Advancements In Grindingmentioning
confidence: 99%
“…The effect of nMQL on normal force and surface roughness with and without ultrasonic vibration is shown in Figures 23 and 24, respectively.
Figure 23. Effect of nMQL with and without UV on normal grinding forces. 193
Figure 24. Effect of nMQL with and without UV on surface roughness. 193
…”
Section: Advancements In Grindingmentioning
confidence: 99%
“…Molaie et al have shown that MQL with water-based nano uids can provide a key value-added quality to ultrasonic vibration-assisted surface grinding. The research also emphasizes the type and concentration of nanoparticles in the base uid and the shape of the nanoparticles and their molecular structures are critical factors impacting the result in the nano lubricant grinding process utilizing ultrasonic vibration [21]. According to Duc et al, in their research about Micro/Nano uids in Sustainable Machining, the performance of nano uids is better than micro uids in reducing cutting temperatures, cutting forces, tool ank wear, and surface roughness of the machined surface [22].…”
Section: Introductionmentioning
confidence: 99%